Peningkatan Pengetahuan melalui Kegiatan Pendampingan bagi Pelaku Usaha Penyembelihan Kuda di Kabupaten Jeneponto - Lestari, Ayu; Abidin, A Mustika; Rusny, Rusny; Jamili, Muhammad Arsan; A, Suci Ananda; Susanti, Handayani Indah; Thaha, Aminah Hajah; Masri, Mashuri (Universitas Nusantara PGRI Kediri, 2024)
Jeneponto Regency is famous for its unique livestock, horses. However, the absence of a halal-certified horse slaughtering place is thought to be related to the low level of knowledge and understanding of horse slaughter business owners regarding halal and thayyib slaughtering. This community service activity involves assistance from expert speakers who discuss halal and thayyib of horse slaughtering. Measurement of participants' level of knowledge after mentoring was carried out through pre-test and post-test. There were 23 questions and 40 respondents consisting of horse slaughter business owners, slaughtermen and other horse slaughter workers. The primary data obtained was the number of participants who answered each question correctly. The results are then tabulated and presented via graph. Paired t-test analysis with SPSS was used to measure the effect of mentoring. The number of respondents who were able to answer questions correctly during the post test was higher or increased compared to the pre test. It can be concluded that assistance to horse slaughter business owners and workers in Jeneponto Regency is effective in increasing participants' knowledge regarding halal and thayyib horse slaughtering.